Teacher’s instructional strategies to support slow learners in selected schools, The Islamic Republic Of Pakistan - Jamshid , Ali Turi; Muhammad Faizal , A. Ghani; Yasir , Javid; Sorooshian, Shahryar (Faculty of Education, University of Malaya, 2017)
Slow learner has been a real challenge for the teacher, especially in the early ages of schooling. This study empirically investigated the impact of instructional strategies adopted by teachers and lecturers at school and college level. Data was collected in a survey was conducted from the teachers and professors in teacher training workshop on the topic of dealing with a slow learner. Results show positive impacts of the teacher supporting instructional strategies including easy use of language, relation development with slow learner, using flexible teaching methodologies, activity based and peer based learning